Bisnis Online: Upaya Peningkatan Pendapatan Perempuan Penerima PKH di Tengah Pandemi Covid-19 - Nazeli Adnan; Sri Andaiyani; Feny Marissa; Fera Widyanata; Zulkarnain Ishak (Universitas Lancang Kuning, 2021)
Indonesia, which is dominated by poor communities, has also been seriously affected not only in the health aspect but also on job losses due to this pandemic. It is hoped that PKH beneficiaries will be able to survive these difficult times. Through the power of housewives who are considered to be able to help the family economy, online business is a new trend today. Therefore, the Sriwijaya University community service activity team provided training related to how to manage an online business. This activity was carried out on November 9, 2020 offline while adhering to health protocols. This training was attended by 40 PKH beneficiaries in Ilir Barat II District, Palembang City, South Sumatra Province. The methods used are presentation, tutoria and discussion. The results showed that 80 percent of participants understood the importance of online promotion through social media. The understanding related to the benefits of social media, types of social media, and downloading applications is quite good where the percentage obtained is above 70 percent. However, understanding regarding the use of Instagram is still lacking where the results only reach 65%. In this case, the government can provide special assistance to women in developing online-based businesses.